Mengenal Investasi: Edukasi Masyarakat untuk Menghindari Investasi “Bodong” di Kecamatan Boliyohuto, Kab. Gorontalo - Nurul Fadhilah; Bela Mamonto; Mustaqim Idrus; Yulfika Daud; Rayyan Mamonto; Tian Lahay; Ranti Amsati; Wahyu Palowa; Rifadli D. Kadir; Iskandar Abbas (Scimadly Publishing, 2023)
Investment aimed to manage assets and increase people's income from the profit earned. The expected return depends on the investment instrument and the level of risk. The higher the risk, the higher the rate of return. On the contrary, the lower the risk, the lower the return on investment. This principle should be well-introduced to the public in order to avoid